'No other faction but my own': dynastic politics and Elizabeth I's Carey cousins - Bundesen, Kristin (2009)
This thesis explores the relationship between kinship networks and Elizabethan politics. Elizabeth I’s Carey cousins, part of the larger Boleyn kinship network, provide the case study. Serving her through three generations dating from before her ascension to her death, Elizabeth enjoyed the benefits and tribulations of the constant presence of her extended family. Extending Elton’s ‘points of contact’ model to include not only court, privy council and parliament but also military and foreign service, allows analysis of the role of kinship networks in Elizabethan government. The gender inclusive nature of kinship networks demonstrates that women participated more fully in the political landscape than has hitherto been accepted. The Carey presence across the extended model provided stability and served as a bulwark against the factionalism so often assumed to have been a leading characteristic of the Elizabethan court. The Careys entered the family business of politics and government and kept Elizabeth within a family context thereby moderating the image of the solitary female ruler Gloriana.